Upaya Peningkatan Hasil Belajar Siswa Kelas VII SMPN 1 Kebumen pada Materi Sejarah Perjuangan Nabi Muhammad SAW melalui Penggunaan Multimedia - Zahrotun Zahrotun (Ta'allum: Jurnal Pendidikan Islam, 2017)
This study aims to improve the learning achievement of historical material of the struggle of Prophet Muhammad SAW through the use of multimedia in the seventh grade students of State Junior High School 1 of Kebumen in academic year 2016/2017. This research is a Classroom Action Research (CAR) using Kemmis and Taggart model consisting of four stages, namely planning, implementation, observation, and reflection. The subject of this research is the students of class VII B SMP N 1 Kebumen. The study was conducted two cycles with data collection techniques such as interviews, observation, documentation and tests. The technique of data validity using triangulation. Data analysis techniques use interactive analysis of Miles and Huberman. The results showed that the use of multimedia can improve the results of learning material history of the struggle of the Prophet Muhammad SAW on students of class VII Junior High School 1 of Kebumen in academic year 2016/2017